The Strategic Role of the Constitutional Court of the Republic of Indonesia Has the Potential to Amend the 1945 Constitution of the Republic of Indonesia (Implications of the Constitutional Court Decision Number 116/PUU-XXI/2023) - Sagalane, Andra Bani; Mandala, Subianta (Pelopor Publikasi Akademika, 2025)
State legal policy reflects the state's interest in securing national objectives through norms that are enacted, implemented, and enforced for the welfare of citizens, state institutions, and all related entities. Article 1, paragraph (3) of the 1945 Constitution of the Republic of Indonesia defines Indonesia as a